2006
DOI: 10.1016/j.jom.2006.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Supplier development: Improving supplier performance through knowledge transfer

Abstract: The dynamic business environment today requires organizations to effectively use all available resources to remain competitive. The quality and cost of a product or service offered in the market is a function, not only of the capabilities of the firm, but also the supplier network providing inputs to the enterprise. To remain competitive, organizations are increasingly implementing supplier development programs to maintain capable and high performance supply bases. This paper presents a conceptual model of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
532
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(563 citation statements)
references
References 70 publications
(114 reference statements)
24
532
0
7
Order By: Relevance
“…Szulanski (1996, p. 36) identifies "an arduous relationship between the source and the recipient" as one of the main reasons firms may fail in transferring best practices between each other. She emphasizes the importance of personal interaction for knowledge exchange, especially where tacit knowledge is concerned (i.e., knowledge that exists only implicitly within individuals; see Modi and Mabert, 2007). Without regular communication, suppliers may receive less feedback on their sustainability progress, thereby reducing goal effectiveness, in accordance with GST (Locke and Latham, 2002).…”
Section: Spatial Distancementioning
confidence: 99%
“…Szulanski (1996, p. 36) identifies "an arduous relationship between the source and the recipient" as one of the main reasons firms may fail in transferring best practices between each other. She emphasizes the importance of personal interaction for knowledge exchange, especially where tacit knowledge is concerned (i.e., knowledge that exists only implicitly within individuals; see Modi and Mabert, 2007). Without regular communication, suppliers may receive less feedback on their sustainability progress, thereby reducing goal effectiveness, in accordance with GST (Locke and Latham, 2002).…”
Section: Spatial Distancementioning
confidence: 99%
“…SDPs have been studied in the USA (Carr et al, 2008;Krause, Handfield, & Tyler, 2007;Modi & Malbert, 2007;Prahinski & Benton, 2004;Wagner & Krause, 2009), Hong Kong (Li et al, 2007), Japan (Sako, 2004) and Germany (Ghijsen, Semeijn, & Ernstson, 2010;Wagner, 2011); and in developing economies such as Mexico (Arroyo-Lopez, Holmen, & Boer, 2012), Brazil (Lakshman & Parente, 2008) and India (Govindan, Kannan, & Haq, 2010). The context of this study is the automotive industry, which marks the most common industry context for SDP research.…”
Section: Supplier Development Programmesmentioning
confidence: 99%
“…Prahinski and Benton (2004) also highlight how the frequency and direction of communication and the degree of feedback can also vary in respect of the different aims of a supplier development programmes. One way communication can disseminate codified information whereas matters such as "quality delivery and flexibility" (Krause, Handfield, & Tyler, 2007, p.533) are more likely to require feedback and more collaborative two-way communication (Modi & Malbert, 2007). However, the concept of knowledge transfer is difficult to capture.…”
Section: : Communication and Knowledge Transfer In Supplier Devementioning
confidence: 99%
“…In this perspective, it is suggested that supplier development efforts should be linked to the model's dimensions, differentiating among efforts to improve supplier's capabilities and efforts to increase supplier's willingness, dealing with the main underlying causes of a supplier's inefficiency. Several supplier development activities have been mentioned in literature (Krause 1999;Krause et al 1998Krause et al , 2000Modi and Mabert 2007;Krause and Ellram 1997), and categorization is suggested based on their effect on these two dimensions, as follows:…”
Section: Managerial Implicationsmentioning
confidence: 99%